Fractured Orthodoxy: The Apocalypticism of the Russian World (Russkii Mir) Theology - Goodin, David K. (Journal of the Council for Research on Religion)

(untitled) (Council for Research on Religion, 2024)
The Russian World (Russkii Mir) theology is at the heart of the invasion of Ukraine, and is fueling the ongoing war with apocalyptic rhetoric. Specifically, the Patriarch Kirill (Gundiaev), Patriarch of Moscow and all Rus’ and Primate of the Russian Orthodox Church, has declared the “special military operation” in Ukraine to be a Holy War, and sees the Russian Federation as the prophesied one restraining the reign of the Antichrist (2 Thessalonians 6–7). The West, and its permissive culture of secularist governments, religious pluralism, reproductive freedom, and acceptance of LGBTQIA+ persons, is seen as literally satanic – that is, as heralding the coming of the Antichrist from the Book of Revelation. This article traces the evolution of this aberrant theology, as well as the geopolitical contexts in which it has evolved. The article concludes with a counternarrative coming from the Orthodox Church Father, Saint Irenaeus of Lyon (☦︎ 202 CE). It is hoped that a “Return to the Fathers” in theological worldview will, in turn, help Russian Orthodoxy to return to sanity, and away from its dangerous apocalyptic rhetoric.